The Effect Positive of Learning Agility on Salespeople Turnover Intention in The Automotive Sector - Aulia Khoirunnisa; Usman (Neo Journal of economy and social humanities, 2024)
This research aims to examine and analyze the influence of job satisfaction, learning agility and work engagement on salespeople turnover intention in the automotive sector. This study uses a quantitative approach, collecting data from 113 respondents in a sample using questionnaires. Structural Equation Modeling - Partial Least Square (SEM-PLS) with SmartPLS 3.0 software was used for data analysis and hypothesis testing in this research.. The findings of research on turnover intention show that job satisfaction and learning agility have a direct and significant influence on turnover intention. Meanwhile, the results of research on employee engagement do not have a significant direct influence on turnover intention, and work engagement cannot mediate between job satisfaction and learning agility on sales force turnover intention in the automotive sector.